Keserupaan Dengan Yesus Dalam Penderitaan, Kesengsaraan Dan Kematian-Nya - Lewi Nataniel Bora (Manna Rafflesia, 2020)
Following Jesus has risks that must be faced. Everyone who will enter into fellowship with Him will be challenged. That challenge to “take up the cross” was presented by Jesus when He was in the world. Everyone who follows Him, will experience suffering. The suffering faced is not the result of a grievous error, but because of the differences between the self-gratifying normal of the previous situation to the self-denying that Jesus calls us too. A person is required to imitate Jesus in facing the various suffering from self-denying that results from his fellowship with Jesus. A person who can endure suffering will continue to be in fellowship with Jesus. Fortitude in dealing with such situations will lead to similarity with Jesus. Similarity is an important part of fellowship with Jesus.